The Paradox of Authenticity : Folklore Performance in Post-Communist Slovakia - Feinberg, Joseph Grim (Book collections on Project MUSE., 2018)
During the Communist reign in Slovakia the state government staged a public performance of stage folklore that was both simplistic and artificial. Recently, as part of a larger movement to retrieve their culture, young Slovakian folklore enthusiasts have attempted to recover an authentic form of rural dance and music, and return their folklore traditions to the Slovakian public by researching, learning, and presenting original, authentic folklore performances. Joseph Feinberg sets out to analyze this contemporary movement with a special focus on its ideology, practices, and performances. But he also tackles a much larger issue. Interpreting the Slovakian movement against a wider background of post-Communist contemporary Central and Eastern Europe, he investigates the issue of authenticity itself, and how a self-identified form of authentic folklore is reconstructed and reenacted.